2014
DOI: 10.1016/j.ygyno.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer clinical trial endpoints: Society of Gynecologic Oncology white paper

Abstract: Objective To explore the value of multiple clinical endpoints in the unique setting of ovarian cancer. Methods A clinical trial workgroup was established by the Society of Gynecologic Oncology to develop a consensus statement via multiple conference calls, meetings and white paper drafts. Results Clinical trial endpoints have profound effects on late phase clinical trial design, result interpretation, drug development, and regulatory approval of therapeutics. Selection of the optimal clinical trial endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 47 publications
1
49
0
Order By: Relevance
“…However, it has proven exceptionally difficult to show a statistically significant prolongation of OS with the addition of targeted therapy to standard treatments in patients with ovarian cancer [10][11][12][13][14][15][16][17][18][26][27][28]. Potential confounding factors for OS include the long postprogression survival period, the administration of multiple postprogression therapies, and the potential for postprogression crossover [27,29]. In the TRINOVA-1 study, 47% of patients had received at least two lines of postprogression therapy, and 14% received an antiangiogenic therapy after progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has proven exceptionally difficult to show a statistically significant prolongation of OS with the addition of targeted therapy to standard treatments in patients with ovarian cancer [10][11][12][13][14][15][16][17][18][26][27][28]. Potential confounding factors for OS include the long postprogression survival period, the administration of multiple postprogression therapies, and the potential for postprogression crossover [27,29]. In the TRINOVA-1 study, 47% of patients had received at least two lines of postprogression therapy, and 14% received an antiangiogenic therapy after progression.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, ovarian cancer patients are treated over the course of many years. 24 Great interest has been observed lately in using observation data to explore primary treatment for EOC. Such studies are limited by both selection bias and the influence of multiple measured and unmeasured confounders that influence both treatment selection and outcomes.…”
Section: Neoadjuvant Chemotherapy In Epithelial Ovarian Cancermentioning
confidence: 99%
“…For example, in a phase II maintenance study of the poly (ADP-ribose) polymerase inhibitor (PARPi) olaparib in patients with recurrent platinum-sensitive high-grade serous ovarian cancer (HGSC), 23% of patients in the control arm ultimately received a PARPi off study, and an OS benefit was not observed even in the setting of a marked PFS improvement (19,20). Because of the difficulties in attaining OS benefits and hence the lack of drug approvals in the United States for ovarian cancer, achievement of significant PFS benefit as a reason for drug approval has been endorsed (21,22), and this has been a mechanism for drug approval in cancers other than ovarian cancer (23,24). In addition, trials that demonstrate a PFS benefit but no OS improvement must define a clinically and statistically meaningful PFS improvement, document patient benefit using patient-reported outcomes and quality-of-life measures, and demonstrate acceptable acute and long-term toxicities.…”
Section: On the Horizonmentioning
confidence: 99%
“…The worldwide incidence of this cancer is 225,500 diagnoses per year; in the United States in 2014, 21,980 women will be diagnosed with ovarian cancer (1,2). Global mortality of this cancer remains high, with 140,200 deaths per year, and minimal improvement in mortality has been observed over the past decade (5).…”
Section: Introductionmentioning
confidence: 99%